IMPLEMENTASI METODE ANALYTICAL HIERARCHY PROCESS PEMILIHAN PROMOTOR TERBAIK DI PT. ACCENTUATES - Wardani, Hadidtyo Wisnu (SKANIKA: Sistem Komputer dan Teknik Informatika, 2024)
The problems that occur at PT Accentuates as a research site are the difficulty of performance evaluation in choosing the best promoter, the data processing procedure is still manual, the selection results are less accurate, and the assessment becomes less objective. So the research proposed using the AHP (Analytical Hierarchy Process) method to determine the best promoter. With observations, interviews and literature studies, and using two calculations, namely manually and applications for accurate data. Based on the research, SPK (Decision Support System) with AHP Method can help the process of selecting the best promoter, the weighting of each criterion, more accurate and precise, brings a high level of transparency, reduces subjective bias and increases objectivity. Web-based SPK application system is the result of this research can be accessed anytime and anywhere. The research results ranked the top 3 values for the June 2023 period, namely Yogi Firdaus = (0.4222), Yosep T.A = (0.2182), Nova S.W = (0.1691). SPK with AHP Method can help Admin and Head of Division at PT Accentuates in choosing the best promoter by providing a printed report of ranking results.